Learning Factors Affecting Social Literacy of Elementary School Students; A Systematic Literature Review - Nabila Yumna; Linda Zakiah; Mahmud Yunus (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to identify learning factors influencing the social literacy of elementary school students through a Systematic Literature Review (SLR) approach. The research protocol was guided by the PRISMA guidelines, utilizing databases including Google Scholar, ERIC, SINTA, Semantic Scholar, and Garuda. A total of 309 articles were initially identified, and following a systematic four-stage screening process, 20 articles met the established inclusion criteria and were analyzed through thematic analysis and content analysis. The findings reveal four primary learning factor clusters: active learning methods and instructional models (40%), social capital support and school climate (25%), innovative learning media and technology (20%), and curriculum programs and school literacy movements (15%). This study concludes that a holistic and integrative approach encompassing collaboration among teachers, educational institutions, families, and policymakers is an essential prerequisite for sustainably optimizing the social literacy of elementary school students.